Glucosinolates from Broccoli By-Products Obtained by Pressurized Liquid Extraction Exert Anti-Inflammatory Activity on Non-Malignant Colonic Myofibroblasts - María Borja-Martínez; Jesús Lozano-Sánchez; Rosa Quirantes-Piné; Lorena Almagro; María A Pedreño; Ana B. Sabater-Jara (Plants)
Broccoli agro-industries generate a significant amount of waste, which leads to both environmental and economic problems. These by-products are typically discarded, despite being a valuable source of bioactive compounds, including glucosinolates (GSLs), which can modulate oxidant and inflammatory mediators, exerting anti-inflammatory properties. A crucial challenge in the exploitation of broccoli agro-industrial by-products is the development of sustainable and green extraction technologies. In this work, pressurized liquid extraction (PLE) based on response surface methodology (RSM) has been developed and optimized for the GSLs’ extraction, with the aim to evaluate the potential protective mechanisms triggered by GSLs-enriched extracts from broccoli by-products in CCD-18Co myofibroblasts exposed to lipopolysaccharide (LPS). The results obtained showed that the PLE is an efficient and environmentally sustainable alternative procedure for extracting GSLs from broccoli by-products. Furthermore, the GSLs-enriched extract obtained through PLE exhibited antioxidant and anti-inflammatory properties in LPS-stimulated cells, being able to attenuate the expression of some proinflammatory markers (IL-1β, IL-6, IL-8, and TNF-α). Therefore, these compounds could serve as potential nutraceutical agents for the prevention and mitigation of oxidative and inflammatory processes related to intestinal bowel diseases, while also promoting the valorization of these by-products.